O RECURSO AO DISCURSO DO OUTRO EM TEXTOS DE ALUNOS DE LETRAS - Matencio, Maria de Lourdes Meirelles (Intercâmbio, 2010)
Based on the principle that the production of reviews is a fundamental activity in the formal professional education, this work analyses reviews written by students from a first language teacher program to reflect about the enunciation process in the rewriting of academic texts.